Comparative proteomic and transcriptomic profile of Staphylococcus epidermidis biofilms grown in glucose-enriched medium - Carvalhais, Virgínia Maria Dinis (2015)
Staphylococcus epidermidis is an important nosocomial agent among carriers of indwelling medical devices, due to its strong ability to form biofilms on inert surfaces. Contrary to some advances made in the transcriptomic field, proteome characterization of S. epidermidis biofilms is less developed. To highlight the relation between transcripts and proteins of S. epidermidis biofilms, we analyzed the proteomic profile obtained by two mechanical lysis methods (sonication and bead beating), associated with two distinct detergent extraction buffers, namely SDS and CHAPS. Based on gel electrophoresis-LC-MS/MS, we identified a total of 453 proteins. While lysis with glass beads provided greater amounts of protein, CHAPS extraction buffer allowed identification of a higher number of proteins compared to SDS. Our data shows the impact of different protein isolation methods in the characterization of the S. epidermidis biofilm proteome. Furthermore, the correlation between proteomic and transcriptomic profiles was evaluated. The results confirmed that proteomic and transcriptomic data should be analyzed simultaneously in order to have a comprehensive understanding of a specific microbiological condition.